In the wake of the crisis: Pension reforms in eight European countries - Karl Hinrichs (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2015)
The 2008 financial market crisis, followed by the Great Recession and sovereign debt crises in several EU countries have triggered drastic reforms of old-age security systems. They were supposed to ensure the financial viability of public pension schemes in the short and long run and/or to realize notions of intergenerational fairness. Most urgently, however, was regaining room for fiscal manoeuvre and obtaining financial aid from supranational organizations (such as IMF or EU). These pension reforms differ from previous changes with regard to their scope and the political process. (1) They were large, thus causing a substantial and immediate impact on the living conditions of present and future retirees and, sometimes, changed the hitherto pursued policy direction. (2) The post-2008 reforms swiftly passed the legislative process and were implemented at short notice. Hence, they can be considered as "rapid policy changes". This paper analyses pension reforms in eight crisis-shaken EU countries: Greece, Hungary, Ireland, Italy, Latvia, Portugal, Romania, and Spain. It explores both reform contents and circumstances which led to the respective changes or facilitated them. As is shown, the challenges, which those countries were (or still are) confronted with, allowed or enforced alterations that would not have been feasible otherwise, or which would rather not have been initiated by the respective governments with regard to the political consequences. Moreover, cross-national comparison reveals similarities and differences and also sheds light on the social consequences that are already visible today. – – Die Finanzmarktkrise von 2008 und in deren Gefolge die Große Rezession sowie Staatsschuldenkrisen in verschiedenen EU-Ländern haben einschneidende Reformen der Alterssicherungssysteme ausgelöst, welche die Finanzierung der Renten kurz- und langfristig sicherstellen und/ oder Vorstellungen von Generationengerechtigkeit realisieren sollen. Dringlicher war es jedoch, den fiskalischen Manövrierspielraum wieder zu erweitern und Kredithilfen von internationalen Geldgebern (IWF, EU) zu erlangen. Diese Rentenreformen unterschieden sich von früheren im Hinblick auf den Umfang und den politischen Prozess. (1) Sie waren groß, zeitigten demzufolge eine signifikante und unmittelbare Wirkung auf die Lebensbedingungen der jetzigen und künftigen Rentenbezieher, und manchmal wurde auch die bis dahin verfolgte Politikausrichtung verändert. (2) Die nach 2008 erfolgten Reformen passierten rasch den Gesetzgebungsprozess und wurden ohne lange Übergangsfristen umgesetzt. In diesem Papier werden die Rentenreformen in acht krisengeschüttelten EU-Ländern betrachtet, nämlich Griechenland, Irland, Italien, Lettland, Portugal, Rumänien, Spanien und Ungarn. Dabei geht es um die Inhalte dieser Reformen und die Umstände, die jeweils zu diesen Veränderungen geführt bzw. sie ermöglicht haben. Gezeigt wird, dass die Herausforderungen, mit denen diese Länder konfrontiert waren (oder sind), einschneidende Veränderungen erlaubten bzw. erzwangen, die ansonsten kaum durchsetzbar gewesen oder in Anbetracht der politischen Konsequenzen von den jeweiligen Regierungen so nicht in Angriff genommen worden wären. Weiterhin werden im Ländervergleich die Gemeinsamkeiten und Unterschiede beleuchtet sowie nach den bislang erkennbaren sozialen Konsequenzen gefragt.
Keywords: 300